Law and the New Institutional Economics: Water Markets and Legal Change in California, 1987-2005 - Jedidiah Brewer; Michael A. Fleishman; Robert Glennon; Alan Ker; Gary Libecap (Washington University Journal of Law & Policy, 2008)
New Institutional Economics (NIE) focuses on the interaction between legal (formal and informal) institutions and economic behavior. Both directions of causality concern researchers in the field: how institutions influence economic behavior and how economic factors affect institutional change. As such, the NIE abandons standard neoclassical economics assumptions that individuals have perfect information about the market and important current or future events, as well as the assumption that transaction costs of exchange are zero. As a result, NIE introduces observed organization and information costs to neoclassical analysis, thereby providing more analytical richness and power for examining empirical activities. In the spirit of the NIE, we examine the interactions among regulation, property rights, and water markets in California from 1987–2005. We are interested in whether and how the definition of water rights and the regulation of water transfers have affected observed market activity in the extent and pattern of water trades and their duration, and the nature of the contracts used (short-term leases, long-term leases, and sales).
Keywords: Water transfer; Water rights; Economics & amp; environmental law; Institutional economics; Water supply; California; United States